Validating the testing of solar air collectors under simulated radiation - San Mateo, Jesus Amado A. (1988, 1988)
This thesis seeks to validate the use of indoor testing of solar air collectors under simulated solar radiation. By conducting performance tests under a solar simulator and comparing the results with those obtained from outdoor testing, the accuracy of indoor testing can be determined. Since most of the established and accepted test procedures are designed for outdoor testing under clear sky conditions in temperature climates, the ability to conduct tests indoors eliminates the variability in weather conditions, a serious problem in conducting tests in the Philippines.
Three existing test procedures were studied, and an original test was developed which simplified data collection. Outdoor tests were conducted and data gathered on ambient temperatures, air temperatures and solar radiation. Equations were generated with these data to predict the outlet air temperature as a function of solar radiation and ambient air temperature. These equations were then applied to the data collected under simulated solar radiation to determine the accuracy of the predictor equations. It was found that by taking a three period moving average of the solar radiation values, a linear equation could predict the air exit temperature.
Thesis (M.S. Energy Engineering)--University of the Philippines Diliman.
Typescript.
Keywords: Solar energy -- Research. -- Philippines; Solar Air Conditioning -- Philippines; Solar radiation -- Philippines